A study on the immediate effects of enhanced external counterpulsation on physiological coupling - Liu, Hongyun; Liang, Hui; Yu, Xiaohua; Han, Yi; Wang, Guojing; Yan, Muyang; Wang, Weidong; Li, Shijun (Frontiers in Neuroscience, 2023)
Introduction Enhanced external counterpulsation (EECP) is a non-invasive assisted circulation technique for its clinical application in the rehabilitation and management of ischemic cardiovascular and cerebrovascular diseases, which has complex physiological and hemodynamic effects. However, the effects of EECP on the coupling of physiological systems are still unclear. We aimed to investigate the immediate effects of EECP on the coupling between integrated physiological systems such as cardiorespiratory and cardiovascular systems. Methods Based on a random sham-controlled design, simultaneous electrocardiography, photoplethysmography, bio-electrical impedance, and continuous hemodynamic data were recorded before, during and after two consecutive 30 min EECP in 41 healthy adults. Physiological coupling strength quantified by phase synchronization indexes (PSI), hemodynamic measurements and heart rate variability indices of 22 subjects (female/male: 10/12; age: 22.6 ± 2.1 years) receiving active EECP were calculated and compared with those of 19 sham control subjects (female/male: 7/12; age: 23.6 ± 2.5 years). Results Immediately after the two consecutive EECP interventions, the physiological coupling between respiratory and cardiovascular systems PSIRES–PTT (0.34 ± 0.14 vs. 0.49 ± 0.17, P = 0.002), the physiological coupling between cardiac and cardiovascular systems PSIIBI–PTT (0.41 ± 0.14 vs. 0.52 ± 0.16, P = 0.006) and the total physiological coupling PSItotal (1.21 ± 0.35 vs. 1.57 ± 0.49, P = 0.005) in the EECP group were significantly lower than those before the EECP intervention, while the physiological coupling indexes in the control group did not change significantly (P > 0.05). Conclusion Our study provides evidence that the PSI is altered by immediate EECP intervention. We speculate that the reduced PSI induced by EECP may be a marker of disturbed physiological coupling. This study provides a new method for exploring the mechanism of EECP action and may help to further optimize the EECP technique.